Increased risk of glacial mudflows origin in Kabardino-Balkaria in the recent period - I. V. Malneva; N. K. Kononova (Лëд и снег, 2015)
The paper deals with probability of glacial mudflow formation during the nearest years in the highland of Central Caucasus where the most mudflow-hazardous rivers are concentrated: Gerhozhansu, Adylsu, Adyrsu and others. It is established on the basis of calculated multi-year air temperatures during summer period that in June–August of 2012–2013 considerable increase and can intensify the activity of glacial mudflows. We estimate the tendency in mudflow activity using the analysis of multi-year regime of atmospheric circulation, the types of which determine mudflow-hazardous weather on a given territory (e.g. 12a, 13s, etc. according to the classification of B.L. Dzerdzeevsky). The duration of these types is presently sufficiently long and will remain the same during the nearest years. Due to the above-mentioned weather situation and availability of sufficient amounts of loose-clastic rock material on the territory of Kabardino-Balkaria, an increase of mudflow hazard is possible. So, in 2011 the glacial-flash mudflows happened in the basins of the rivers Cherek Balkarsky, Chegem, Baksan. In all these cases the weather corresponded to the type of ECM 13s. In 2013 the increase in duration of the above-mentioned ECM and mudflow activity can be connected with maximum of the solar cycle. During the previous maximum in 2000 the catastrophic mudflow happened on the river Gerhonzhansu; the town Tyrnyauz have been highly destructed.